Peran Artificial Intelegence (AI) dalam Mempersonalisasi Pengalaman Pelanggan - Dadang Irawan; Benardi Benardi; Hanifah Hanifah (Universitas Maritim AMNI Semarang, 2025)
This study examines the role of Artificial Intelligence (AI) in personalizing customer experiences, focusing on the benefits, challenges, and opportunities presented by this technology. AI enables companies to enhance operational efficiency while creating more personalized customer experiences through deep data analysis. The technology provides relevant product and service recommendations, optimizes every stage of the customer journey, and improves engagement and satisfaction. The research was conducted through webinars involving various groups, including academics, practitioners, and the general public. The findings indicate that AI implementation offers significant benefits, such as improved operational efficiency and customer satisfaction. However, ethical, privacy, and data security challenges require a responsible implementation approach. With a strong ethical framework, AI can continue to be developed to support innovation without compromising customer rights protection.